O002 Diabetes-associated HLA donor genotypes and pancreas transplant outcomes. (22nd July 2022) - Owen, RV; Counter, C; Shaw, JA; Wilson, CH; White, SA
Abstract: Introduction: The genotypes HLA DR3/DR4, DR3/DR3, DR4/DR4 are associated with a predisposition to diabetes. This study evaluated UK recipient outcomes after pancreas transplantation from donors with a diabetes-associated genotypes. Methods: Data on all UK pancreas transplants from 2004–2019 was obtained from the NHSBT-UK Registry, n=2, 938. HLA-DR type was recorded for all organ donors. Re-transplants and those missing patient (PS) or graft (GS) survival were excluded, resulting in a final cohort of n=2, 661. We further delineated our categories into SPK, PTA and PAK as a previous study suggested different recipient categories may be adversely affected. Univariate analyses were conducted using Kaplan-Meier plots and multi-variate analysis using Cox-regression models. Complications were analysed using chi-squared analyses. Results: The majority of grafts were from donors not associated with diabetes genotypes (90.1%, n=2397) whereas 5.4%(n=145) came from HLA DR3/DR4 donors, 1.6%(n=43) from DR3/DR3 and (n=76)2.9% from DR4/DR4. Comparable outcomes for GS at 1yr (SPK p=0.980, PTA p=0.759, PAK p=0.244) and 3yrs (SPK p=0.708, PTA p=0.744, PAK p=0.275) and PS at 1yr (SPK p=0.553, PTA p=0.527, PAK p=0.756) and 3yrs (SPK p=0.728, PTA p=0.928, PAK p=0.424) were seen. Multivariate analysis also showed no statistically significant difference in GS (p=0.604, HR 1.041, 95%CI 0.895, 1.211) or PS (p=0.623, HR 1.045, 95%CI 0.876, 1.248). There were comparable complication rates. Conclusion: This multicentre UK study has found comparable survival outcomes and complication rates within our donor-HLA-genotype groups. We do not believe that the presence or absence of a diabetes associated HLA-genotype influences outcomes for any category of pancreas transplant. Take-home message: We do not believe that the presence or absence of a diabetes-associated HLA-genotype influences outcomes for any category of pancreas transplant.